Implementation of a Free Inclusive Program for Children with Disabilities at Rumah Anak Prestasi (RAP) Kedung Cowek Surabaya City - Putri, Prizalia Berliana; Rining Nawangsari, Ertien (Jurnal Kebijakan Publik, 2025)
This study provides an indepth examination of the implementation of health services and skills training programs at Rumah Anak Prestasi (RAP) Kedung Cowek in Surabaya. It focuses specifically on the provision of free services for children with disabilities. The background of this research arises from the increasing number of children with special needs (ABK) in society, coupled with the economic constraints faced by many families in accessing essential health services and skill training opportunities. RAP Kedung Cowek serves as a vital alternative, offering a range of free services, including eye examinations, ENT check-ups, occupational therapy, and various creative training programs, all at no cost to the families. The research employs a qualitative descriptive approach, utilizing data collection techniques such as in-depth interviews, direct observation, and documentation. Data analysis is conducted using George C. Edwards III's implementation theory from the book Implementing Public Policy, which encompasses dimensions of communication, resources, disposition, and bureaucratic structure. The findings of this research indicate that the implementation of the program has been facilitated through inter-party coordination, the strategic use of digital media, and the strong commitment of the implementers. However, several challenges persist, including communication that has not yet been fully optimized, despite showing signs of improvement, and a bureaucratic structure that lacks written Standard Operating Procedures (SOPs) and clarity in task distribution. This study underscores the importance of strengthening the communication system within the program to enhance its overall performance and reach.